Impact Assessment of the National Adaptation Programme of Action (PANA) on Strengthening the Capacity-Building and the Resilience of Farming Households to Climate Change in Benin - Akpovi, S.C.; Vissoh, P.V.; Aoudji, A.N.; Awali, A. Issa; Fanou-Fogni, N.; Vodouhe, S.D. (European Scientific Journal, ESJ, 2026)
This study analysed the impact of the integrated climate change adaptation programme to strengthen farming households’ capacity-building and resilience on agricultural production, food, and nutrition security in Benin. The research was carried out in the nine most vulnerable communes to climate change in Benin: Malanville, Ouaké, Savalou, Aplahoué, Sô-Ava, Ouinhi, Matéri, Bopa, and Adjohoun. A combined qualitative and quantitative approach was used to collect data from eighteen villages (nine beneficiary and nine control villages) through group discussions and individual interviews using checklists and structured questionnaires. Using a counterfactual approach, 508 respondents (i.e., 254 beneficiaries and 254 non-beneficiaries) were interviewed. Data analysis comprised descriptive statistics, food and nutrition indicators, analysis of variance, and logistic regression. The assessment of food insecurity indicators in the communes revealed moderate to severe levels of food insecurity. There were significant differences between beneficiary and non-beneficiary households in both food and nutritional security (p<0.05) and food insecurity (p<0.05). Female-headed households had a higher probability of experiencing food insecurity (15.15%) compared to male-headed households (8.56%). Binary logistic regression results indicated that age, gender, and education were the determinants of food security status. Furthermore, the dietary diversity assessment indicated that beneficiary households of the integrated climate change adaptation programme had more diverse diets (23.94%), consuming less than four dietary groups per day, compared to non-beneficiary ones (30.92%). These results clearly show that the interventions of the climate change adaptation programme have strengthened the capacity building of farming households towards sustainable agriculture and food security. The study recommends that government development programmes should be more gender-sensitive.